Teaching and learning Operational Amplifiers using a reconfigurable and expandable kit - Costa, Ricardo (2019)
Operational Amplifiers (OpAmps) are one of the most important integrated circuits in the area of electronics. These type of devices are widely adopted in the area since they allow the design of simple and/or complex analogue circuits without many efforts. It is therefore fundamental to create innovative educational solutions to facilitate their teaching and learning, and in particular the inclusion of more experimental work in a course curricula. For this purpose, it was designed and implemented a reconfigurable and expandable kit to teach and learn electronic circuits based on the OpAmp uA741. The kit comprises a software application and a hardware platform. The software application allows the simulation and the reconfiguration of real electronic circuits based on the OpAmp uA741 included in the hardware platform. For measuring and/or applying signals to a particular reconfigured circuit, users may establish automatic connections. In this paper it is described the features and functionalities provided by the kit, and an overview about the OpAmp uA741. At the end, some teachers’ opinions about their perceptions concerning a possible adoption of the kit in a real educational scenario are presented.